2020
DOI: 10.1097/brs.0000000000003798
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Hounsfield Units at the Planned Upper Instrumented Vertebrae May Predict Proximal Junctional Kyphosis in Adult Spinal Deformity

Abstract: Study Design. Retrospective cohort study. Objective. To investigate the association between Hounsfield units (HU) measured at the planned upper instrumented vertebra (UIV) and UIV+1 and proximal junctional kyphosis (PJK) in patients with adult spinal deformity (ASD). Summary of Background Data. PJK is a common complication following surgery for ASD and poor bone quality is noted to be one of the risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 34 publications
5
41
0
Order By: Relevance
“…The L1 vertebral body is commonly chosen for DXA, and it has an indicated threshold value of 110 for detecting osteoporosis and 135 for detecting osteopenia 7 . In the case of ASD patients, several studies have indicated that PJK is associated with lower HU values at the UIV or UIV + 1, 8–10 and HU <120 was a significant risk factor for PJF 8,10 . On the contrary, it is not clear how much increase in HU values is anticipated after TPTD treatment in cases of ASD surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The L1 vertebral body is commonly chosen for DXA, and it has an indicated threshold value of 110 for detecting osteoporosis and 135 for detecting osteopenia 7 . In the case of ASD patients, several studies have indicated that PJK is associated with lower HU values at the UIV or UIV + 1, 8–10 and HU <120 was a significant risk factor for PJF 8,10 . On the contrary, it is not clear how much increase in HU values is anticipated after TPTD treatment in cases of ASD surgery.…”
Section: Discussionmentioning
confidence: 99%
“…7 In the case of ASD patients, several studies have indicated that PJK is associated with lower HU values at the UIV or UIV + 1, 8-10 and HU <120 was a significant risk factor for PJF. 8,10 On the contrary, it is not clear how much increase in HU values is anticipated after TPTD treatment in cases of ASD surgery. Mikula et al 14 showed that TPTD treatment increased the average HU and BMD of the lumbar spine (L1 to L4) by 22% and 9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post hoc analysis demonstrated significantly lower mean HU in the osseous PJK group than in the non-osseous PJK group. Patients with ≤120 HU had a risk of osseous PJK that was 5.74 times higher compared with those with >120 HU 10 .…”
Section: Deformitymentioning
confidence: 90%
“…Based on a study from our institution, a UIV with a HU of 120 or less is at high risk for junctional failure. 18 Therefore, we try to select a UIV with an HU of >120, extending into the upper thoracic spine if necessary. During surgery, meticulous end plate preparation is a must, and safe decancellation of any visual posterior elements should also be done.…”
Section: Goals Of Minimally Invasive Surgery Deformity Correctionmentioning
confidence: 99%